Glasbene preference vzgojiteljev in predšolskih otrok - Denac, Olga (Revija za elementarno izobraževanje, 2012)
Music Activity Preferences of Preschool Teachers and Children. The objective of the survey involving preschool teachers and children aged five to six was to explore the interest of teachers and pupils towards music activities. We established that the preschool teachers concerned were most interested in musical activities such as singing, playing musical instruments, and listening to music. As for children, their favourite activities, that is, the ones they wanted to participate in, were movement to music, song singing, and playing musical instruments. These are the activities that make them active participants in the educational process. We can assume that a teacher’s interest in a music activity influences the frequency of the activity being included in lesson plans, and children’s interest in music depends on the teacher expressing their interest in music activities.